Aortic Cross‐Clamping to Provide Differential Fixation by Perfusion. Issue 3 (19th March 2021) - Moore, Mackenzie M.; Alejandro, Emilyn U.
Abstract: An intricate network of regulation between the brain and the pancreas modulates hormone secretion and organ function. Dysfunction of the brain‐pancreas axis occurs in disease states such as diabetes and pancreatitis. Given the delicate nature of the mouse brain, procurement for tissue and cellular analysis is facilitated by fixation by perfusion with paraformaldehyde (PFA). The brain is hardened by PFA during the preservation process, but this hardening also occurs in the pancreas, as well as the remainder of the intra‐abdominal organs. This hardening makes the pancreas friable and difficult to dissect without damaging and fragmenting the organ. Additionally, this fixation may preclude the ability to perform analytic techniques such as western blot and quantitative PCR (qPCR) simultaneously. Performing a simple cross‐clamping of the thoracic aorta allows for differential perfusion of organs and maximal use of limited samples from a single animal. The brain can be perfused with PFA without compromising tissue collection of the pancreas and other intra‐abdominal organs. This simple maneuver allows for greater tissue collection and analysis per mouse in studies evaluating the brain‐pancreas or brain‐gut axis. © 2021 Wiley Periodicals LLC. Basic Protocol : Differential fixation by perfusion using aortic cross‐clamp